2001
DOI: 10.1053/ejvs.2001.1369
|View full text |Cite
|
Sign up to set email alerts
|

A Model for National Outcome Audit in Vascular Surgery

Abstract: this study has shown that P-POSSUM methodology can be used to predict outcome after arterial surgery across a range of surgeons in different hospitals and could form the basis of a national outcome audit. It was also possible to obtain accurate models for both mortality and major morbidity from the POSSUM physiology scores alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(40 citation statements)
references
References 13 publications
1
39
0
Order By: Relevance
“…In 2001 the Vascular Surgical Society of Great Britain and Ireland conducted an audit of 1345 vascular operations. One finding was that the physiological element of the POSSUM score predicted outcome of surgery as well as the total score with the operative element [35]. Neary et al showed that the POSSUM physiology score alone could predict the outcome of intra-arterial thrombolysis for acute leg ischaemia [36] and the same group in 2003 showed that the physiological POSSUM score predicted outcome for ruptured AAA surgery [37].…”
Section: Pre-operative Scoring Systemsmentioning
confidence: 99%
“…In 2001 the Vascular Surgical Society of Great Britain and Ireland conducted an audit of 1345 vascular operations. One finding was that the physiological element of the POSSUM score predicted outcome of surgery as well as the total score with the operative element [35]. Neary et al showed that the POSSUM physiology score alone could predict the outcome of intra-arterial thrombolysis for acute leg ischaemia [36] and the same group in 2003 showed that the physiological POSSUM score predicted outcome for ruptured AAA surgery [37].…”
Section: Pre-operative Scoring Systemsmentioning
confidence: 99%
“…[6] was recommended as the most appropriate for general surgery [7,8]. This model, utilizing scores relating to twelve physiological and six operative variables, was developed to predict in-hospital mortality and morbidity postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…To counteract these limitations, specialty-specific models based on the POSSUM methodology have been developed and applied in arterial surgery 11,12 (V-POSSUM) and oesophagogastric surgery (O-POSSUM) 10 .…”
Section: Introductionmentioning
confidence: 99%